SISTEM PENDUKUNG KEPUTUSAN SELEKSI BANTUAN DANA HIBAH PENELITIAN DENGAN METODE ANALYTIC NETWORK PROCE (ANP): (Studi Kasus : Lembaga Penelitian dan Pengabdian Pada Masyarakat (LP2M) Universitas Muhammadiyah Palangkaraya) - Haryadi Haryadi; Citra Amalia; Doddy Teguh Yuwono; Fitri Amalia Sholehah; Santika Santika (Jurnal Informatika dan Rekayasa Elektronik, 2021)
At the end of 2019, the ranking for research was issued by the Ministry of Research, Technology and Higher Education at that time, UM Palangkaraya moved up the rankings from the fostered cluster to MADYA. This encourages the institution to further improve the quality of research quality from lecturers. One of them is by providing Penelitian Penelitian Kompetitif Dosen Interna (PKDI). For this reason, research programs carried out in tertiary institutions are required to produce high quality and useful products. The manifestation of this openness is that program proposals received by LP2M will be reviewed by the assessment team (peer review) and then declared accepted or rejected for funding. However, the current assessment process is still carried out manually, namely by looking at certain criteria only, regardless of other assessment criteria. Of course, the manual assessment process is very likely to make mistakes. Therefore, a Web-based Decision Support System (DSS) was built using the Analytic Network Process (ANP) method. Based on the results of the research, it can be seen that the developed SPK can make it easier to assess the feasibility of proposing proposals at UM-Palangkaraya effectively and objectively in obtaining Grants based on the weights and predetermined criteria.